Relationship between thyroid function and lipid atherogenic profile in pediatric patients with multisystem inflammatory syndrome associated with COVID-19 - Calcaterra, Valeria; De Santis, Raffaella; Braghieri, Davide; Zanelli, Sara; Zuccotti, Gianvincenzo (Frontiers in Pediatrics, 2024)
Introduction Concurrent alterations in the metabolic profile and thyroid dysfunction, including nonthyroidal illness syndrome (NTIS) has been reported in multisystem inflammatory syndrome in children (MIS-C). Considering the influence of thyroid hormones (TH) on lipid metabolism, we explored the relationship between thyroid function and the atherogenic lipid profile in children with MIS-C at admission and during a 12-month follow-up.Patients and Methods we considered children admitted for MIS-C. Total and HDL cholesterol, triglycerides (TG), fasting plasma glucose, fasting plasma insulin as well as free T3 (FT3), free T4 (FT4), and TSH were assessed at diagnosis within 24 hours of admission and during follow-up. TG/HDL ratio, no-HDL/HDL ratio and atherogenic index of plasma was also considered as atherogenic risk markers.Results we monitored 56 children. On admission, pathological levels of FT3, FT4, TSH, TG, TC, HDL, TG/HDL ratio, no-HDL/HDL ratio, and AIP were detected. Correlation analyses revealed associations between FT3, FT4, and lipid markers and TSH with TG. During monitoring, while complete restoration of TH balance was achieved at 12 months, some patients still exhibited an altered lipid profile, without correlation between thyroid function and lipid markers.Conclusions we supported a relationship between thyroid function and an atherogenic lipid profile in children with MIS-C. This may result from interactions between adaptive and innate metabolic responses and genetic predisposition. Elucidating the relationship between TH and metabolic pathways during infections could help identify new biomarkers to prevent acute and fatal outcomes, improving patient prognosis and protecting long-term health.